Lipid Profile of Broilers Fed Zinc Bacitracin on Plant and Animal Protein Diets - Ogboko, Benson (International Journal of Poultry Science, 2011)
This investigation was undertaken to determine the effect of protein sources and growth promoter Zinc bacitracin on the lipid profile of broiler chickens. Two trials were conducted, comprising of 240 day-old chicks and 120 day-old chicks respectively, they were housed in battery cages in a broiler pen, randomly distributed into four (4) major groups each receiving diets with protein derived from plant or animal protein with or without the addition of Zinc bacitracin. The plant and animal diets were compiled, milled and analysed, before been subdivided into two subgroups with Zinc bacitracin included at 300 g per tonne. The feeding trial lasted for six (6) weeks. On terminating the feeding trial, 30 marked birds from each group were slaughtered and blood samples were analysed for, total cholesterol, triglyceride, HDL and LDL. There was a significant difference (p<0.05) in the broiler plasma cholesterol levels, as observed in total cholesterol, HDL and LDL cholesterol levels while there was no significant difference in the triglyceride levels. Animal protein diet induced the highest cholesterol levels but on addition of Zinc bacitracin the level was reduced, as was also the case in plant diets. Reduction of plasma cholesterol levels on the inclusion of Zinc bacitracin could indicate that cholesterol is been deposited in the tissues.